1991
DOI: 10.1089/aid.1991.7.97
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Conserved Regions of the Major Core Protein (gag24) of HIV-1 and HIV-2

Abstract: Five mouse monoclonal antibodies were raised against a recombinant protein comprising the complete sequence of gag24 protein from HTLV-IIIB. All monoclonal antibodies recognized the native protein in enzyme-linked immunosorbant assay (ELISA) and Western blots. All monoclonal antibodies also cross-reacted with an human immunodeficiency virus type 2 (HIV-2) strain in western blots, whereas only one antibody detected HIV-2 p25 in ELISA. By using synthetic peptides, cross-reacting epitopes were mapped and three re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…1 c, clones p24-14 and p24-16). This region almost overlaps with the epitope identified with MAbs by two other groups (Carpio et al, 1991;Niedrig et al, 1991). Recently, Niedrig et al (1991) reported the characterization of 27 MAbs directed against p24 proteins of HIV-1 and HIV-2.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…1 c, clones p24-14 and p24-16). This region almost overlaps with the epitope identified with MAbs by two other groups (Carpio et al, 1991;Niedrig et al, 1991). Recently, Niedrig et al (1991) reported the characterization of 27 MAbs directed against p24 proteins of HIV-1 and HIV-2.…”
mentioning
confidence: 61%
“…This indicates that the site could be one of the immunodominant epitopes of this core protein. Inhibition experiments using human sera by Carpio et al (1991) showed that this region is also immunogenic in humans. Moreover both MAbs are presumed to be broadly cross-reactive with various HIV isolates and also with SIVAcM, suggesting applicability to the detection of the p24 antigen in the sera of HIV-l-infected patients.…”
mentioning
confidence: 99%
“…These include two dominant peptides located in the aminoterminal portion of the molecule, and 10 peptides located in the carboxy-terminal portion of the Gag protein. The amino-terminal region is known for its antigenic properties [32][33][34] and has been reported to contain both B and T-cell epitopes and to be relatively conserved among European HIV-1 isolates [33,35]. The carboxyterminal region is also known to bind antibodies developed during natural HIV-1 infection in humans [36].…”
Section: Discussionmentioning
confidence: 99%
“…The epitope recognized by the anti-p24 MAbs was localized to p24 peptide 16 (aa 152 to 172) (data not shown). The production of MAbs directed against epitopes overlapping the N or C terminus of peptide 16 has recently been reported (Hinkula et al, 1990;Carpio et al, 1991 ;Niedrig et al, 1991). Since all these MAbs cross-react with HIV-1, in contrast to the anti-p24 MAbs presented here, they probably recognize different epitopes.…”
Section: Abteilung Virologie Und Immunologie Deutsches Primatenzentmentioning
confidence: 99%